The specific story is a guide to the exception among the commentators in Adam and Jesus (peace be upon them both (Journal of the College of Basic Education, 2022)
The wording of the news indicating the investigation was enriched and highlighted in many places of the Noble Qur’an showing constancy and continuity, in a way which is right, whereby them it has been followed the path of generalization with specification, thumb, and clarification, outlining and detailing, thus through the news the specialization and the generalization, and that the specificity in the news is a statement for What is not mentioned in general terms. In addition to that, the whole prophets are servants of Allah Almighty who are created like the rest of the people and born of male and female except Adam and Jesus, for Adam, Allah created him from dust in his hand neither male nor female, and Jesus created him in the womb of his mother without a male, and people are a name that unites Adam and Jesus and those between them and after them. On the authority of God Almighty when this news was revealed that it did not mean Adam and Jesus, peace be upon them both, regarding the people whom He created, male and female. Because that special report was presented in Adam and Jesus, peace be upon them, and the word’s output was general in them and without them, and its meaning is specific to people without them. The Almighty Allah mentioned that He created people from a male and a female, and did not explain how he created both of them, but he showed that in other places in the Quraan, and revealed that Adam has been created by dust, then showed the levels that dust passed through as became constant mud, black spoiled, and clay as pottery.